2016
DOI: 10.1259/bjr.20150912
|View full text |Cite
|
Sign up to set email alerts
|

Parotid gland lesions: separate and combined diagnostic value of conventional MRI, diffusion-weighted imaging and dynamic contrast-enhanced MRI

Abstract: The parotid lesions with ill-defined margin, adjacent tissue infiltration, cervical lymphadenopathy, ADC ≤1.01 × 10(-3) mm(2) s(-1) and plateau TIC pattern are more likely to be malignant. The diagnostic value of conventional MRI would be increased when DWI is applied in combination, whereas additional DCE-MRI did not improve differential ability of conventional MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 26 publications
3
52
2
Order By: Relevance
“…20,21 Some previous studies reported that diffusion-weighted imaging (DWI) and its derived apparent diffusion coefficient (ADC) could provide high diagnostic accuracy in characterizing parotid gland tumors, but there was significant overlap in ADC values among different tumors. [22][23][24] Therefore, there is still no consensus on the role of DWI in characterizing parotid gland tumors.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Some previous studies reported that diffusion-weighted imaging (DWI) and its derived apparent diffusion coefficient (ADC) could provide high diagnostic accuracy in characterizing parotid gland tumors, but there was significant overlap in ADC values among different tumors. [22][23][24] Therefore, there is still no consensus on the role of DWI in characterizing parotid gland tumors.…”
Section: Discussionmentioning
confidence: 99%
“…During our study design, we tried a highly-optimized imaging parameter. Thirty slices with a slice thickness of 3 mm were used in our study, while the slice thickness usually ranged from 4 to 6 mm in previous studies [1,2,21]. The voxel size was 1.1 × 1.1 × 3.0 mm 3 , and the average number of each b value was set as 2.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion weighted imaging (DWI) is a widely-used technique for evaluating the rate of microscopic water diffusion in tissues. Its derived apparent diffusion coe cient (ADC) has been accepted as an important diagnostic marker for characterizing parotid gland tumors [1,2]. In clinical practice, single-shot echoplanar imaging (SS-EPI) is commonly used for DWI scan.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of MRI can be even more increased with the complement of dynamic contrast-enhanced MRI (DCE-MRI), diffusion-weighted imaging (DWI), and apparent diffusion coefficient (ADC) calculation. [ 22 23 24 ]…”
Section: Ross-sectional I Maging mentioning
confidence: 99%
“…Even DWI and ADC, in the differentiation of benign and malignant nodules, showed similar features and conflicting results among different studies. [ 24 28 ]…”
Section: Ross-sectional I Maging mentioning
confidence: 99%